Health related quality of life of Canary Island citizens - Lopez-Bastida Julio; Oliva-Moreno Juan; Worbes-Cerezo Melany; Serrano-Aguilar Pedro (BMC, 2010)
Abstract Background The aim of the study was to describe the health-related quality of life of Canarian population using information from the Canary Island Health Survey and three observational studies developed in the Canary Islands. Methods A descriptive analysis was carried out on a sample of 5.549 Canarian citizens using information from 2004 Canary Island Health Survey and three observational studies on Alzheimer's disease, Stroke and HIV. EQ-5 D was the generic tool used for revealing quality of life of people surveyed. Besides the rate of people reporting moderate or severe decrease in quality of life, TTO-index scores and visual analogue scale were used for assessing health related quality of life of people that suffer a specific diseases and general population. Results Self-perceived health status of citizens that suffer chronic diseases of high prevalence, identifies by the Canary Island Health Survey and other diseases such Alzheimer's disease, Stroke and HIV, independently examined in observational studies, are worse than self-perceived health of general population. Depression/anxiety and pain/discomfort were identified as the dimensions of the EQ-5 D with highest prevalence of problems. Alzheimer's disease and stroke were the illnesses with greater loss of quality of life. Conclusions Health related quality of life should be integrated into a set of information along with expectancy of life, incidence and prevalence of chronic diseases for developing health policy and planning health care activities The combination of information on health related quality of life from population health surveys with data from observational studies enlarges the sources of relevant information for setting health priorities and assessing the impact of health policies.